Is the proteinuria an independent predict factor for diabetic kidney disease progression? (Research, Society and Development, 2022)
Objective: To identify the association between proteinuria and the progression of kidney disease. Methods: A retrospective cohort study that analyzed the medical records of patients who attended a nephrology outpatient clinic between 2016 and 2021. Patients over 18 years, diagnosed with diabetes mellitus (DM) and who had data available in their medical records during the entire evaluation time, were included. Clinical variables (type of DM, duration of DM, systemic arterial hypertension (SAH), dyslipidemia, alcohol consumption, smoking, use of antiproteinuric drugs) and laboratory variables (renal function, blood glucose, glycated hemoglobin, counting blood cells) were evaluated. In the statistical analysis, binary logistic regression, backward and the forward types were used, performed in SPSS version 25 and with a significance level of 5%. Results: 384 patients were eligible for the study and 142 were patients with DM. Among these, 33 patients met all inclusion criteria and 31 (93.9%) had type 2 diabetes. A prevalence of proteinuria was observed in 24 patients (72.4%) at baseline. Of the sample, 30 (90.9%) were using antiproteinuric drugs, 18 (54.5%) had renal disease progression and simultaneous proteinuria during the follow-up. Only four patients did not present proteinuria during the study period. It is important to note that there was no significant association between proteinuria and renal function worsening. Conclusion: proteinuria was not significantly associated with Glomerular Filtration Rate (GFR) and, therefore, was not confirmed as an independent predict factor for the evolution of diabetic kidney disease (DKD).